HM-SPCA: Hybrid Method for Automatic Detection of MA Using MinIMas with Sparse PCA in Diabetic Retinopathy - Sankari, A; kumar, D. Ashok (International Journal of Computer Sciences and Engineering, 2025)
Microaneurysms (MAs) is an earliest lesions in DR detection, its plays a challenging role in diabetic retinopathy (DR) diagnosis. It has been an active research in medical image processing and so many machine learning algorithms has been developed for MA detection. The First Stage of detection is consisting of clearer segmentation of optical disc area in retina using a new Minimum Intensity Maximum Solidity (MinIMas) algorithm on fundus dataset, then extract bright lesion and red lesion using Gaussian mixture models. Set of feature extracted that the second stage of the system, finally machine learning approach is a0pplied for lesion classification. In this paper, a hybrid of segmentation and unsupervised classification of sparse PCA (HM-SPCA) for MA detection is proposed so that enhanced output is obtained. This proposed algorithm achieves great analysis in lesion segmentation with minimum false alarm. Furthermore, effective features can be extracted due to sparse properties of PCA (Principle Component Analysis) which merge the elastic net penalty with PCA together. Thus, the projected DR detection system enhanced its performance by reducing false positives compared with existing algorithms in lesion classification, and hence this approach can be applied to improve the beneficence in earlier vision detection of patients for diabetic retinopathy